Molecular and serological rapid tests as markers of Trypanosoma cruzi infection in dogs in Costa Rica - Lizundia, Regina (2014)
Chagas disease is a zoonotic disease caused by Trypanosoma cruzi and dogs are one of the main domestic reservoirs. Materials and Methods: One molecular (OligoC‑TesT, Coris Bioconcept) and one serological (T. cruzi‑Detect, Inbios) rapid tests were evaluated as infection markers for T. cruzi in 102 dogs living in eight villages endemic for Chagas in Costa Rica. Results: T. cruzi‑Detect performed well as screening tool with 23.3% positive samples. The large number of invalid results (66.7%) observed in samples tested with OligoC‑TesT precluded assessing the use of this new method as epidemiological tool to detect T. cruzi infection in dogs.